Identification of novel uracil derivatives incorporating benzoic acid moieties as highly potent Dipeptidyl Peptidase-IV inhibitors. Issue 4 (15th February 2019) - Huang, Junli; Deng, Xiaoyan; Zhou, Siru; Wang, Na; Qin, Yujun; Meng, Liuwei; Li, Guobao; Xiong, Yuhua; Fan, Yating; Guo, Ling; Lan, Danni; Xing, Junhao; et al.
Graphical abstract: Abstract: Dipeptidyl Peptidase-IV (DPP-4) is a validated therapeutic target for type 2 diabetes. Aiming to interact with both residues Try629 and Lys554 in S2 ′ site, a series of novel uracil derivatives 1a –l and 2a –i incorporating benzoic acid moieties at the N3 position were designed and evaluated for their DPP-4 inhibitory activity. Structure-activity relationships (SAR) study led to the identification of the optimal compound 2b as a potent and selective DPP-4 inhibitor (IC50 = 1.7 nM). Docking study revealed the additional salt bridge formed between the carboxylic acid and primary amine of Lys554 has a key role in the enhancement of the activity. Furthermore, compound 2b exhibited no cytotoxicity in human hepatocyte LO2 cells up to 50 μM. Subsequent in vivo evaluations revealed that the ester of 2b robustly improves the glucose tolerance in normal mice. The overall results have shown that compound 2b has the potential to a safe and efficacious treatment for T2DM.